2021
DOI: 10.3389/fvets.2021.670811
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Changes in Total and Differential Milk Cell Counts, Activity, and Expression of Milk Phagocytes of Healthy and Mastitic Indigenous Sahiwal Cows

Abstract: Milk somatic cell counts (SCCs) have been used as a gold standard to monitor mammary health as well as an indicator of raw milk quality. The present work was undertaken to compare the changes in the milk SCC, milk differential leukocyte counts (DLCs), phagocytic activity (PA) of milk neutrophils and macrophages (by nitroblue tetrazolium assay), extracellular trap formation (PicoGreen assay) and mRNA expression of various genes in milk neutrophils and macrophages (reverse transcription–polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…The present study divided camel milk leukocytes based on their differential expression of the cell surface molecules CD172a and CD14 into a dominant CD172a + /CD14 low /SSC high granulocyte population followed by a smaller fraction of CD172a + /CD14l high /SSC high macrophages and a minor CD172a − /CD14 − /SSC low lymphocytes population. The higher proportion of granulocytes in camel milk, compared to other species like bovine ( 17 , 28 ), could be a result of their dominance in peripheral blood ( 49 ). The results of the present study, however, largely correspond to data reported for goats regarding the differential composition of milk cells ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present study divided camel milk leukocytes based on their differential expression of the cell surface molecules CD172a and CD14 into a dominant CD172a + /CD14 low /SSC high granulocyte population followed by a smaller fraction of CD172a + /CD14l high /SSC high macrophages and a minor CD172a − /CD14 − /SSC low lymphocytes population. The higher proportion of granulocytes in camel milk, compared to other species like bovine ( 17 , 28 ), could be a result of their dominance in peripheral blood ( 49 ). The results of the present study, however, largely correspond to data reported for goats regarding the differential composition of milk cells ( 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The milk somatic cell count and the CMT are widely accepted tools for the evaluation of the mammary gland health status ( 17 , 28 ). In camels, elevated SCC values were observed in milk samples from infected mammary glands with values ranging from 1 × 10 5 to 10 × 10 6 cells/ml milk ( 8 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations